Separatist movements in southern Thailand : Pattani United Liberation Organisation (PULO) 2004-2010 - Kumar, R. Suresh (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The unrest in Southern Thailand has attracted serious attention regionally and internationally. The provinces of Pattani, Yala and Narathiwat are the most affected areas compared to Satun and Songkhla, witnessing almost daily killings and bombing. To date, 4800 people have died. The on-going unrest has created much confusion and endless speculation. The acts of violence seem mindless and indiscriminate to observers who have not examined the historical, political, and economic suppression, and ideological beliefs of the people in Southern Thailand. These factors may lead groups and organisations to have differences in their daily modus operandi to achieve its objective. The groups in Southern Thailand are often linked with members of ethnic minorities. One of the groups that is linked in the ongoing conflict is Pattani United Liberation Organisation (PULO). This study will examine the organisation structure of PULO, their strategies, tactics and target selections in achieving their political objectives. Besides that, the study will also examine the relevance of PULO to Thai politics in general. This study is descriptive in nature and data collections are done through secondary sources and interviews. Finally, in the conclusion chapter, the study indicated that PULO‟s involvement is vague. Besides that, this study could be a guide to authorities from Malaysia and Thailand to work together to bring peace and formulate a better conflict management / resolution to resolve the conflict in the deep south